2010
DOI: 10.1007/s00018-010-0544-y
|View full text |Cite
|
Sign up to set email alerts
|

POU homeodomain protein OCT1 modulates islet 1 expression during cardiac differentiation of P19CL6 cells

Abstract: Islet 1 (ISL1), a marker of cardiac progenitors, plays a crucial role in cardiogenesis. However, the precise mechanism underlying the activation of its expression is not fully understood. Using the cardiac differentiation model of P19CL6 cells, we show that POU homeodomain protein, OCT1, modulates Isl1 expression in the process of cardiac differentiation. Oct1 knock-down resulted in reduction of Isl1 expression and downregulated mesodermal, cardiac-specific, and signal pathway gene expression. Additionally, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 42 publications
1
15
0
Order By: Relevance
“…The pCDNA3.1-c-MYC, c-MYC-luc, and mutant-c-MYC-luc reporters were constructed previously by our laboratory [30]. The CCNB1-luc, CCNB2-luc, mutant-CCNB1-luc, and mutant-CCNB2-luc reporters were constructed by TransGen Biotech (Beijing, China).…”
Section: Methodsmentioning
confidence: 99%
“…The pCDNA3.1-c-MYC, c-MYC-luc, and mutant-c-MYC-luc reporters were constructed previously by our laboratory [30]. The CCNB1-luc, CCNB2-luc, mutant-CCNB1-luc, and mutant-CCNB2-luc reporters were constructed by TransGen Biotech (Beijing, China).…”
Section: Methodsmentioning
confidence: 99%
“…However, it is unknown how p-STAT3 and p-c-Jun control ISL-1 expression. Bioinformatic analysis showed that the core transcriptional regulatory region of ISL-1 (-1000 ~ ATG) [30] contains conserved p-STAT3 and p-c-Jun binding sites (Figure  8A). Luciferase assay with ISL-1-luc , a ISL-1 luciferase reporter construct containing the binding site of c-Jun and STAT3, was performed in Ly3 cells treated with IL-6/STATTIC (JAK/STAT signaling activator/inhibitor) or Anisomycin/SP600125 (JNK signaling activator/inhibitor), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The plasmid transfection and luciferase activity detection were performed as described before [30]. ISL-1-luc plasmid was constructed previously by our laboratory [30].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations